Britain in the Thirties - Wright, Basil; Massingham, Richard; Braun, Vivian; Cavalcanti, Alberto; Elton, Arthur; Anstey, Edgar; Lye, Len; MacLaren, Norman; Biggar, Helen; Jennings, Humphrey (BFI, 2000)
Compilation of British avant-garde films from the 1930s. Includes Len Lye's 'The Birth of the Robot', Norman McLaren's 'Hell Unltd', Arthur Elton and Edgar Anstey's 'Housing Problems', Basil Wright's 'Song of Ceylon', and Alberto Cavalcanti's 'Coal Face', as well as work by Richard Massingham, B. Vivian Braun, Humphrey Jennings, and the London Kino Group. [www.amazon.co.uk]